Synchronous Occurrence of Splenic Pleomorphic Mantle Cell Lymphoma and Esophageal Adenocarcinoma with Overexpression of BCL1 Protein - Dominik Dabrowski; Roberto F. Silva; Michael Constantinescu; Rodney E. Shackelford; Nestor Dela Cruz; Eric X. Wei (Case Reports in Oncological Medicine)
Synchronous occurrences of mantle cell lymphoma (MCL), or intermediate lymphocytic lymphoma, and other malignancies are rare. Such cases present diagnostic and especially therapeutic challenges, making them of particular interest to study. We report a case of synchronic MCL and an esophageal tumor in an elderly male patient. Morphologically, the tumors were classified as splenic pleomorphic MCL and adenocarcinoma of the esophagus occurring concurrently. The pleomorphic MCL mimicked diffuse large B cell lymphoma (DLBCL) but lacked larger centroblast- or immunoblast-like cells. Curiously, both tumors overexpressed cyclin D1 by immunohistochemistry. This is an important feature that distinguishes MCL pathologically from two of its closest entities in the differential diagnosis: chronic lymphocytic leukemia and DLBCL, the latter of which mantle cells cannot transform into. The lymphoproliferation revealed IGH/CCND1 translocation by FISH, but the esophageal adenocarcinoma only showed CCND1 aneuploidy without break-apart signals. Since the gastrointestinal (GI) tract is a common site of extranodal involvement by MCL and lymphomatous polyposis can present as GI polyps, adequate care was taken to differentiate the esophageal adenocarcinoma from advanced stagings of MCL, as well as metastatic adenocarcinoma. Despite numerous immunohistochemical stainings studied, only BCL1 was demonstrated to have partial overlap in both tumors. The patient underwent esophagectomy and splenectomy. A subsequent metastatic primary lung squamous cell carcinoma was diagnosed, after which the patient expired. MCL typically presents at an advanced stage and has been deemed incurable with a prognosis of only several years. It is unclear whether the patient succumbed to complications of his MCL or the metastatic squamous cell carcinoma. Furthermore, he was lost to follow-up for a year and only received treatment after his third cancer was diagnosed. We have reviewed previous reports of synchronic mantle cell lymphoma and other solid tumors or hematological malignancies in the literature.